2009
DOI: 10.3171/2009.4.peds08309
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic intracystic hemorrhage in pineal cysts

Abstract: Pineal cysts are benign and often asymptomatic intracranial entities. Occasionally they can lead to neurological symptoms through growth or due to intracystic hemorrhage. The purpose of the current report is to describe their clinical characteristics and treatment options. In the current study, the authors illustrate the course of disease in 3 patients who developed neurological symptoms due to hemorrhage into a pineal cyst. Two of their patients had additional cerebral disease, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 30 publications
0
24
0
4
Order By: Relevance
“…It may be associated with an increased likelihood of symptomatic presentation, 5,19,20,49,58,63 and sudden death from pineal hemorrhage with acute hydrocephalus has been reported. 41,55 Fleege et al 20 found fluid-fluid levels consistent with previous hemorrhage in 3 of 19 patients who presented with symptomatic pineal cysts.…”
Section: Discussionmentioning
confidence: 99%
“…It may be associated with an increased likelihood of symptomatic presentation, 5,19,20,49,58,63 and sudden death from pineal hemorrhage with acute hydrocephalus has been reported. 41,55 Fleege et al 20 found fluid-fluid levels consistent with previous hemorrhage in 3 of 19 patients who presented with symptomatic pineal cysts.…”
Section: Discussionmentioning
confidence: 99%
“…Although the vast majority of pineal cysts, even large ones, can be expected to be found incidentally and remain asymptomatic (1), some patients may present with signs and symptoms of increased intracranial pressure or focal signs and symptoms due to compression and edema in neighboring structures (2, 3). Pineal apoplexy is generally considered to be rare (1,(4)(5)(6). Most patients with pineal apoplexy have been reported to have relatively severe symptoms that often accompany acute occlusive hydrocephalus (4-6) and may occasionally result in sudden death (11) or the need for surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of these cysts are benign and are usually asymptomatic, some are occasionally associated with headaches, hydrocephalus, extraocular movement abnormalities and Parinaud's syndrome (2,3). The hemorrhage of a pineal cyst, which is sometimes referred to as pineal apoplexy, is considered to be rare and is often associated with severe symptoms (4)(5)(6). We herein describe an adult case of chemical meningitis induced by an intracystic hemorrhage of the pineal region in which the patient presented with clinical manifestations resembling bacterial meningitis and was able to achieve a benign outcome without any surgical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pineal cysts often show a thin (no greater than 2mm) rim of enhancement upon contrast due to surrounding pineal parenchyma, which lacks a blood-brain barrier 5 . Pineal tumors on the other hand, have been reported to typically appear similar to grey matter on MRIs 5,6 . In all our cases, appearances in CT and MRI were indicative of blood derivate content within the lesion, which obscured its appearance, hindering identification of the pathological process underlying the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Pineal cysts appear strongly hyperintense to brain parenchyma and often CSF on T2-weighted images 1,5,6 . In addition, pineal cysts often show a thin (no greater than 2mm) rim of enhancement upon contrast due to surrounding pineal parenchyma, which lacks a blood-brain barrier 5 .…”
Section: Discussionmentioning
confidence: 99%